I have some Questions, that i need help with, explaining how to do them for myself would be a huge help.
How would i simplify this equation?
‑3 x a x b - 5 x a x ‑b
I have to find the value of this expression: 2x2 - 3y + 5 when x = 2 and y = ‑3
Simplify 5a 2 - 4ab 2 - 2a 2 + 6ab 2
Expand and then simplify:
a. 4(3 + 2x - y) - 2(5 - x + 3y)
b. a(3b + x) + b(2a - y)
well i cant help in all..but i know some..
5a 2 - 4ab 2 - 2a 2 + 6ab 2
is 3a2 + 2ab2
a. 4(3 + 2x - y) - 2(5 - x + 3y)
b. a(3b + x) + b(2a - y)
12 + 8x - 4y - 10 +2x - 6y or 10x - 10y - 2
3ab + ax + 2ab - yb or 5ab + ax - yb
2x2 - 3y + 5 when x = 2 and y = ‑3
uhm is y = .3? or y = 3? if its y = 3 then
2(2)2 - 3(3) + 5 = 4
the first few questions are knowing how to distribute and multiplying. the other one is substitution..